The Socio-Political Dimension of Da'wah in the Qur'an: Thematic Analysis Of The Relationship Between Da'wah and Power - Andieni Putri Olivia Arifin; Abdul Malik Ghozali; Budimansyah Budimansyah; Dzaky Hafizh Muttaqien; Shofiya Fikri Handayani (Universitas Darussalam Gontor, 2026)
This study aims to analyze the socio-political dimension of da‘wah studies in the Qur’an through a thematic examination of the relationship between da‘wah and power. This topic is significant because, in contemporary discourse, da‘wah is often narrowly understood as a purely spiritual or individual activity, whereas the Qur’an presents it as an instrument of social transformation with implications for authority, leadership, and governance. This research employs a thematic (maudhu‘i) method of Qur’anic exegesis by collecting verses related to key concepts such as ḥukm (authority), mulk (sovereignty), amānah (trust), khilāfah (vicegerency), ulī al-amr (legitimate authority), and the principle of al-amr bi al-ma‘rūf wa al-nahy ‘an al-munkar (enjoining good and forbidding evil). These verses are analyzed conceptually and contextually using a normative-qualitative approach. The findings indicate that the Qur’an constructs the relationship between da‘wah and power within an ethical-integrative framework: revelation serves as the source of normative legitimacy, da‘wah functions as a medium of moral transformation, and power operates as an instrument for the realization of social justice. In the Qur’anic perspective, power is not autonomous but constitutes a moral trust bound by justice, accountability, and collective responsibility. These findings underscore the importance of strengthening a transformative paradigm of da‘wah as a conceptual foundation for addressing contemporary socio-political challenges.